Applied Non-Linear Dynamical Systems - Awrejcewicz, Jan.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
The book is a collection of contributions devoted to analytical, numerical and experimental techniques of dynamical systems, presented at the International Conference on Dynamical Systems: Theory and Applications, held in Łódź, Poland on December 2-5, 2013. The studies give deep insight into both the theory and applications of non-linear dynamical systems, emphasizing directions for future research. Topics covered include: constrained motion of mechanical systems and tracking control; diversities in the inverse dynamics; singularly perturbed ODEs with periodic coefficients; asymptotic solutions to the problem of vortex structure around a cylinder; investigation of the regular and chaotic dynamics; rare phenomena and chaos in power converters; non-holonomic constraints in wheeled robots; exotic bifurcations in non-smooth systems; micro-chaos; energy exchange of coupled oscillators; HIV dynamics; homogenous transformations with applications to off-shore slender structures; novel approaches to a qualitative study of a dissipative system; chaos of postural sway in humans; oscillators with fractional derivatives; controlling chaos via bifurcation diagrams; theories relating to optical choppers with rotating wheels; dynamics in expert systems; shooting methods for non-standard boundary value problems; automatic sleep scoring governed by delay differential equations; isochronous oscillations; the aerodynamics pendulum and its limit cycles; constrained N-body problems; nano-fractal oscillators; and dynamically-coupled dry friction.
Duffing-Type Oscillators with Amplitude-Independent Period -- Asymptotics of Rigid-Body Motions for Nonlinear Dynamics: Physical In-sight and Methodologies -- Non-Linear Phenomena Exhibited by Flexible Cylindrical and Sector Shells -- Gear Shift Patterns in Uncertain Terrestrial Locomotion Systems -- Turbulence in Flexible Plates and Shells -- Using Bifurcation Diagrams for Controlling Chaos -- Shear Waves Dispersion in Cylindrically Structured Cancellous Viscoelastic Bones -- Quasi-Regular and Chaotic Dynamics of Postural Sway in Human -- Modeling of Ropes with Consideration of Large Deformations and Friction by Means of the Rigid Finite Element Method -- Dynamical Response of a Van Der Pol-Duffing System with an External Harmonic Excitation and Fractional Derivative -- Vortex Structure Around the Cylinder at a Flow of Viscous Fluid -- Asymptotic Analysis and Limiting Phase Trajectories in The Dynamics of Spring Pendulum -- Vibration Surveillance System with Variable Stiffness Holder for Flexible Details Milling -- Diversities in the Inverse Dynamics Problem for Underactuated Mechanical Systems Subject to Servo-Constraints -- Rare Phenomena and Chaos in Switching Power Converters -- Constrained Motion of Mechanical Systems and Tracking Control of Nonlinear Systems -- The General Conception of Intellectual Investigation the Regular and Chaotic Behavior of Dynamical Systems of Special Structure -- Dynamic Properties of Two-Axle Freight Wagon with UIC Double-Link Suspension as a Non-Smooth System with Dry Friction -- Dynamics of Mechanical Systems with Mecanum Wheels -- Reliability Analysis of the Dynamics of a Horizontal Drill-String -- Transition in Oscillatory Behavior in Mouse Oocyte and Mouse Embryo Trough Oscillatory Spherical Net Model of Mouse Zona Pellucida -- Constrained N-Body Problems -- Hunting French Ducks in Population Dynamics -- Model of Nonlinear Fractal Oscillator in Nanosystem -- Dynamical Statement Networks -- The Shooting Method for Non-Standard Boundary Value Problem -- Automatic Sleep Scoring From a Single Electrode Using Delay Differential Equations -- Methods for the Quick Analysis of Micro-Chaos -- Bouncing Ball Dynamics: Simple Motion of the Table Approximating the Sinusoidal Motion -- Periodic Motions of Coupled Oscillators Excited by Dry Friction and Harmonic Force -- Limit Cycle Oscillations of an Aerodynamic Pendulum -- Vibratory Energy Localization by Non-Smooth Energy Sink with Time-Varying Mass -- Coordinate-Free Formulation of Nonholonomic Constraints for Wheeled Robots -- Optomechatronic Choppers with Rotating Elements: Design Programs -- A Delay Mathematical Model for HIV Dynamics in HIV-Specific -- The Application of Parametric Excitation in Resonant MEMS Gyros -- Influence of Smart Materials on the Dynamical Response of Mechanical Oscillator -- Dynamical Pendulum-Like Nonconservative Systems.
Keywords: Dynamics; Ergodic theory; Differential equations; Partial differential equations; Dynamical Systems and Ergodic Theory; Ordinary Differential Equations; Partial Differential Equations